ANALISIS KOMPETENSI DAN ETOS KERJA TERHADAP KINERJA GURU DI SMK NEGERI 2 PEKANBARU - Khairunnas, M. Rizki; Lussianda, Erfa Okta; Yadi, Elmi (Komunitas Manajemen Kompetitif, 2026)
The era of globalization demands that education be capable of producing high- quality human resources who play a vital role in national development. This study aims to analyze the influence of competence and work ethic on teacher performance at SMK Negeri 2 Pekanbaru. The research employed a multiple linear regression method with a sample of 74 teachers. The results of the heteroscedasticity test indicated no signs of heteroscedasticity. Furthermore, both the t-test and F-test confirmed that competence and work ethic have a significant influence, both partially and simultaneously, on teacher performance. The coefficient of determination (R²) of 91.5% shows that competence and work ethic collectively explain a large portion of the variation in teacher performance. These findings emphasize the importance of enhancing competence—particularly in the aspect of personality—and strengthening work ethic, especially discipline, to support optimal teacher performance. The study recommends continuous training and regular evaluations to improve the quality of education at SMK Negeri 2 Pekanbaru.